World supply and demand projections for cereals, 2020 - Agcaoili-Sombilla, Mercedita C.; Rosegrant, Mark W. (International Food Policy Research Institute, 1994)
Future directions of food supply and demand will be determined by the interaction of various market forces (such as prices, population, and income) as they will be affected by decisions and policies of farmers, national governments, and international donors. Considering all these factors, an IFPRI global food model was used to estimate future world prices, supply, demand, and trade of cereals. Results for three scenarios are presented in this brief: a baseline scenario, a scenario where production growth will slow, and a scenario in which, in conjunction with the production growth reduction, income growth will also slow. The model is also capable of simulating other scenarios. The results clearly indicate that it is critical to maintain yield growth rates in developing economies, particularly in Sub-Saharan Africa. Because lower production is associated with income losses, it would be disastrous in developing regions. Higher prices would also have a profound impact on effective demand and the ability of the world's poor, the bottom 20 percent of the world's population, to obtain adequate food supplies.